Pengaruh Waktu Reaksi Transesterifikasi Biodiesel dari Minyak Lemak Ayam dengan Menggunakan Katalis MgO - Habib, Alltop Amri Ya; Suhendri, Suhendri (Journal of Bioprocess, Chemical and Environmental Engineering Science, 2024)
Generally, biodiesel is produced from vegetable oils, however, this raw material has certain drawbacks, such as price fluctuations due to its competing use in the food industry, making it less economical. Therefore, this study utilizes chicken fat oil as an alternative raw material for biodiesel production, using MgO as a catalyst. The biodiesel was produced through a transesterification reaction at a temperature of 60°C, with an oil-to-methanol ratio of 25 ml:30 ml, and 0.5 g of catalyst. The study varied the reaction times, which were 60 minutes, 120 minutes, and 180 minutes. The best result was obtained at a reaction time of 180 minutes, yielding 92.19%. The biodiesel produced had a density of 0.962 g/ml, a viscosity of 2.931 cSt, and a water content of 0.0416%.